Analysis of water absorption in industrial waste of superabsorbent polymer and cellulosic fiber - Barth, Mateus Essvein; Pistore, Mateus Ripol; Brehm, Feliciane Andrade; Mancio, Mauricio; Souza, Vitória da Luz de (Matéria, 2024)
abstract Proper curing of concrete is one of the most important processes in the post-concreting period so that concrete can achieve the desired mechanical strength and durability. However, part of the construction works perform this procedure for inadequate periods or often do not perform it; as a result, surface characteristics are commonly affected, resulting in increased porosity and, consequently, increased permeability, cracking and carbonation. Materials that have water retention capacity and subsequent gradual release may be effective as internal curing agents. Superabsorbent polymers (PSA) are already used and widely studied for this purpose, but usually with commercial origin. The objective of this research is to evaluate different water absorption methods in industrial waste of superabsorbent polymer and cellulosic fiber (PSAR) for later use as an internal curing agent in Portland cement matrices. PSAR was homogenized by a process at two different times. The material in its natural state and homogenized had its absorption capacity evaluated using two methods: ISO 17190:2001 and sieve method. For the sieve method, the influence of hydration time on absorption was analyzed. The ISO 17190:2001 method did not show representativeness in the results due to the high absorption variation. The sieve method was more representative and demonstrated efficiency in the homogenization processes, reducing the coefficient of variation by up to 43%. The material with the highest potential for use was PSAR60, with an absorption value of 68.26 g of water per g of PSAR, since the absorption test showed the highest homogeneity and, from this absorption, no longer had significant variations.